Does the social credit system construction reduce enterprises’ overinvestment? quasi-natural experimental evidence from China - Guozhen Zhang; Yurui Xia; Yiting Xie; Yuanxiang Dong (PLoS ONE, 2025)
As an important part of improving the socialist market economic system, the social credit system focuses on the market’s micro behavior, which emphasizes the credit self-discipline of enterprises in financial management and checks the orientation for enterprises’ investment decisions. This study selected Shanghai and Shenzhen A-share listed companies for 2012–2023 as samples and used the pilot reform of China’s social credit system as a quasi-natural experiment to test the impact and mechanisms of the construction of the social credit system on enterprises’ overinvestment. The main findings show that the social credit system construction alleviates enterprises’ overinvestment behaviors, realized by the inhibiting effect of internal controls, the reverse effect of risk monitoring, and the guiding effect of business environment optimization. Heterogeneity analyses illustrate that the social credit system construction has a more obvious inhibitory effect on overinvestment for enterprises that are less subject to financing constraints, have higher internet penetration, have better financial development levels, are eastern, non-manufacturing, and large-scale. The conclusions provide new perspectives and references for the government and enterprises to re-examine the economic effects of the social credit system construction, which can promote capital usage efficiency and guide enterprises toward rational management.